2015
DOI: 10.1016/j.molmet.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The calcineurin-NFAT pathway controls activity-dependent circadian gene expression in slow skeletal muscle

Abstract: ObjectivePhysical activity and circadian rhythms are well-established determinants of human health and disease, but the relationship between muscle activity and the circadian regulation of muscle genes is a relatively new area of research. It is unknown whether muscle activity and muscle clock rhythms are coupled together, nor whether activity rhythms can drive circadian gene expression in skeletal muscle.MethodsWe compared the circadian transcriptomes of two mouse hindlimb muscles with vastly different circad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 61 publications
(83 reference statements)
7
83
1
Order By: Relevance
“…7 A and B). Importantly, all seven mammalian elongase family members are either rhythmically expressed or their expression is affected by core clock gene alterations in peripheral mouse tissues, with Elovl1, Elovl5, and Elovl6 being circadian in mouse skeletal muscle (5,12,45). Moreover, ACSL4 was shown to be rhythmic in mouse liver, and its rhythmicity was attenuated in ClockΔ19 mutant mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…7 A and B). Importantly, all seven mammalian elongase family members are either rhythmically expressed or their expression is affected by core clock gene alterations in peripheral mouse tissues, with Elovl1, Elovl5, and Elovl6 being circadian in mouse skeletal muscle (5,12,45). Moreover, ACSL4 was shown to be rhythmic in mouse liver, and its rhythmicity was attenuated in ClockΔ19 mutant mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…Circadian activation of calcineurin is not unique to the heart and has also been documented in skeletal muscle [277], as evidenced by changes in Rcan1.4 transcript levels and activity of NFAT reporters. In a series of elegant experiments these investigators demonstrated that circadian activation of the calcineurin/NFAT pathway was independent of the transcriptional circadian clock mechanism, and was driven instead by muscle innervation and contractile activity.…”
Section: Circadian Activation Of Calcineurin In the Heartmentioning
confidence: 99%
“…Several genes are known to regulate catabolism in muscle tissue by activating proteasomal proteolysis of sarcomeric proteins and this is thought to regulate muscle size (Bodine et al, 2001;Witt et al, 2008). Among such genes are those encoding the Muscle RING Finger (Murf) family of Tripartite Motif (Trim) proteins that have been reported to undergo circadian changes in mRNA level in muscle (Amaral and Johnston, 2012;Dyar et al, 2018Dyar et al, , 2015McCarthy et al, 2007). Analysis of murf1/trim63a and murf2/trim55b mRNA levels in 3-5 dpf larvae by qRT-PCR suggested that these genes undergo circadian cycling, such that they peak in every dark phase at ZT15 (Fig.…”
Section: Circadian Induction Of Catabolism At Night Is Suppressed By mentioning
confidence: 99%
“…Previous studies, generally performed on adult rodent limb muscle, indicated that protein synthesis, as reflected by either p70S6K and ERK1/2 phosphorylation (Chang et al, 2016) or puromycin incorporation (Dyar et al, 2018), display a day/night variation in skeletal muscle. In addition, the expression of atrogenes, such as atrogin1 and murf1, were shown to undergo rhythmic circadian changes in skeletal muscle (Dyar et al, 2018(Dyar et al, , 2015McCarthy et al, 2007;Perrin et al, 2018). Some of these circadian differences were shown to be abolished by loss-of-function of core clock genes (Dyar et al, 2018(Dyar et al, , 2015, indicating the critical requirement of the molecular clock in regulating muscle metabolism.…”
Section: Muscle Grows More During Day Than Nightmentioning
confidence: 99%